PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR MATA PELAJARAN IPA MATERI CIRI-CIRI MAKHLUK HIDUP SISWA KELAS III SDN 02 NGAWEN PATI - Oktaviani, Menik Husni (JURNAL SINEKTIK, 2018)
The purpose of this research to find out the influence of learning model Course Review Horay against the results of the study The IPA class 3 SDN 02 Ngawen. Methods used i.e. True-Experimental Designs kind of Pretest-Posttest Control Group Design. Results of the study showed higher rataan posttest has 82.045 on the experimental class and 79.091 rataan on classroom control as well as pretest have rataan value 80.68 class experiments and 58.18 averagedan class controls so that the value of the regression test  and test linieritas  1,89 with 2.85 it was concluded that Fcount < Ftable means H0 accepted ar t linear equations occuring inya , perh i tungan with test signifikanci   887.57 and 4.35 it was concluded that the Freg  >Ftables mean Ho is rejected, meaning significant regression equation diterima. As for the influence of great determination coefficient test results with Microsoft Excel 2013 by 30% while the rest is influenced by the fakother tor. It is said that model learning Horay Course Review effective influence on learning outcomes or IPA students Land 02 Ngawen